INTENSIFICATION OF HEAT- AND MASS TRANSFER IN EVAPORATION - CONDENSATION DEVICES - A. G. Kulakov (Izvestiâ Vysših Učebnyh Zavedenij i Ènergetičeskih ob Edinennij SNG. Ènergetika, 2005)
Results of investigation of capillary structure properties used in evaporation – condensation devices are presented.Constructive solutions for intensification of heat transfer in evaporation and condensation heat exchangers are offered. The obtained heat transfer experimental data at film-type vapor conden-sation are generalized in criterion form.Description of general rule of heat and mass transfer processes in miniature heat pipes with three various capillary structures at wide range of operating parameters is given in the paper.